2002
DOI: 10.1677/joe.0.1720449
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids are not necessary for the inhibitory effect of endotoxic shock on serum IGF-I and hepatic IGF-I mRNA

Abstract: The aim of this work was to elucidate the possible role of glucocorticoids in the bacterial lipopolysaccharide (LPS)-induced decrease in hepatic IGF-I synthesis. For this purpose, we studied the effect of LPS on IGF-I in two rat strains, Wistar and Lewis, which have different adrenal responses to inflammation. Compared with Wistar rats, Lewis rats have a reduced hypothalamic-pituitary-adrenal response to inflammatory stimuli. Rats received two i.p. injections of 1 mg/kg LPS and were killed 4 h after the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
3
12
0
2
Order By: Relevance
“…As previously reported, LPS injections decreased GH receptor and IGF-I mRNAs in the liver (Priego et al 2002a(Priego et al , 2003a. However, in the kidney, LPS did not affect GH receptor gene expression, although it decreased IGF-I gene expression, as in the liver.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…As previously reported, LPS injections decreased GH receptor and IGF-I mRNAs in the liver (Priego et al 2002a(Priego et al , 2003a. However, in the kidney, LPS did not affect GH receptor gene expression, although it decreased IGF-I gene expression, as in the liver.…”
Section: Discussionsupporting
confidence: 82%
“…In these conditions, we found that LPS decreased IGF-I gene expression in the kidney. Furthermore, in chronic inflammation we also found a decrease in renal IGF-I mRNA (Ibáñez de Cáceres et al 2002a).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations